The Nature of Literacy Instruction in Elementary School History Lessons - Khawaja, Amna; Puustinen, Mikko (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2022)
This paper examines literacy-related practices existing in elementary history classrooms and asks to what extent these practices are compatible with the ideals of historical literacy, i.e. disciplinary literacy specific to history. A total of 50 hours were spent observing nine Finnish classrooms. Data sources included numeric data, field notes and classroom artifacts. The results show that the most common text type used was the body text of a textbook while primary sources were few. The textbook was typically addressed as a neutral source of information. Teachers used visual texts only briefly and to support an existing narrative. None of the teachers modeled reading strategies specific to history. The teacher profiles suggest diverse approaches to literacy but the practices used by teachers point more to content-area and cultural literacy than disciplinary literacy. Implications for elementary literacy and history instruction are discussed.